Redox‐Driven Cu─Pd Bond Formation to Enhance the Efficiency for Electroreduction of CO2 to CO. Issue 10 (2nd August 2022) - Lai, Yi-An; Chu, You-Chiuan; Chang, Chia-Jui; Chen, Kuan-Hsu; Hsiao, Yu-Cheng; Chang, Chun-Chih; Liao, Mei-Yi; Chen, Hao Ming
Abstract : The redox reaction as the driving force induces the dynamic structure of the electrocatalyst, which enhances the performance of the catalysis. Yet, it lacks the understanding of the influence of redox driving force on the transforming process, inhibiting obtaining the actual factor that determines the catalytic performance. Resorting to the pulse and in situ methodology, herein, the effect of spontaneous reoxidation on the structural transformation of the Cu–Pd bimetallic catalyst for CO2 electroreduction is investigated. During the pulse program, applying the open‐circuit voltage and cathodic potential intermittently oxidizes and reduces the Cu–Pd bimetallic catalyst, which systematically reveals the catalyst redox reaction imparting the increase in CO2 ‐to‐CO selectivity. Through in situ X‐ray absorption spectroscopy (XAS), the dynamic structure induced by the spontaneous reoxidation is unveiled, suggesting the Cu─Pd bond formation for the bimetallic catalyst with a higher Pd content. Such a reoxidation‐induced Cu─Pd bond enhances the CO faradaic efficiency to 88% with the CO current density of −132 mA cm −2 . By the methodologies, a new perspective is provided to understand the redox‐driven dynamic structure and the corresponding effect on the product selectivity, which is a vital concept to design the new catalysts in the future. Abstract : The influence of redox reaction on the structural transformation of CuPd bimetallic catalyst for electrochemical CO2 reduction reaction is investigated through pulse methodology. By in situ X‐ray absorption spectroscopy analysis, the spontaneous reoxidation inducing Cu─Pd bond formation is revealed to promote the CO production.